Pemberdayaan UMKM Orang Asli Papua Guna Meningkatkan Perekonomian di Kabupaten Merauke - Bismar, Bismar; Teturan, Yohanis E; Maturbongs, Edoardus E (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
Abstract The economic empowerment of local communities, especially Indigenous Papuans, is an important strategy in creating economic independence and reducing social inequality in South Papua. This study aims to describe the role and strategy of local governments in empowering indigenous Papuans through micro, small, and medium enterprises in Merauke Regency. The research method uses a qualitative descriptive approach with data collection through observation and documentation studies. The results of the study indicate that local governments have roles and strategies that can be implemented in efforts to empower indigenous people through the micro, small, and medium business sector in Merauke Regency where this sector plays a significant role in opening up employment opportunities and increasing economic income. However, there are also challenges such as limited access to capital, lack of business assistance, and inappropriate marketing processes are still the main obstacles. Therefore, synergy between the government and stakeholders is needed to support the sustainability of micro, small, and medium enterprises in Merauke Regency for indigenous Papuans in a sustainable manner.